Effect of Periodontal Ligament Stem Cells-Derived Conditioned Medium on Gene Expression and Differentiation of Tumor Necrosis Factor-α-Challenged Osteoblasts - Vongsakulpaisarn, Poranee; Sangkhamanee, Sujiwan Seubbuk; Rassameemasmaung, Supanee; Sritanaudomchai, Hathaitip (European Journal of Dentistry, 2023)
Objectives Tumor necrosis factor-α (TNF-α) causes bone resorption in periodontitis. It induces the production of receptor activator of NF-κB ligand (RANKL) from osteoblasts, leading to the disturbance of bone homeostasis through RANKL, RANK, and osteoprotegerin (OPG) axis. This study aimed to explore the effect of periodontal ligament stem cells-derived conditioned medium (PDLSCs-CM) on gene expression related to bone homeostasis and the differentiation of TNF-α-challenged osteoblasts.Materials and Methods Human osteoblasts were cultured with 50 ng/mL of TNF-α and 0, 1, 10, and 100 µg/ mL of PDLSCs-CM. Osteoblasts cultured without TNF-α and PDLSCs-CM were served as control. Gene expression of RANKL, OPG, and interleukin-1β (IL-1β) was evaluated by reverse transcription quantitative polymerase chain reaction at 48 hours. The early-stage and late-stage differentiation of TNF-α-challenged osteoblasts without or with PDLSCs-CM was explored by alkaline phosphatase (ALP) activity and alizarin red staining, respectively, at day 1, 3, 6, 9, and 12.Statistical Analysis Mann–Whitney U test was used to analyze the differences in gene expression of TNF-α-challenged osteoblasts at 24 and 48 hours, and Kruskal–Wallis test was used to analyze the effect of PDLSCs-CM on gene expression and ALP activity among all experimental groups using SPSS software version 21.0. Statistical significance was considered with p-value less than 0.05.Results Expression of RANKL, OPG and IL-1β was significantly upregulated in TNF-α-challenged osteoblasts compared to the untreated control. The PDLSCs-CM at 1 and 10 μg/mL downregulated gene expression of TNF-α-challenged osteoblasts compared to the group without PDLSCs-CM, but the difference did not reach statistical significance. The ALP activity was decreased in TNF-α-challenged osteoblasts. The addition of PDLSCs-CM did not alter ALP activity of TNF-α-challenged osteoblasts. Alizarin red staining was comparable in the TNF-α-challenged osteoblasts cultured without or with PDLSCs-CM.Conclusions The PDLSCs-CM did not alter gene expression involved in bone homeostasis and differentiation of TNF-α-challenged osteoblasts.
Keywords: conditioned medium; mesenchymal stem cells; osteoblasts; osteoprotegerin; RANKL; tumor necrosis factor-alpha